Uogólniony Plaski Stan Naprężenia w Wirującym Lepkosprężystym Dysku ze Sprężystym Pierścieniem - J. Kossecki (Engineering Transactions, 1964)
The object of the paper is to investigate the state of stress and strain in a disc made of a visco-elastic-material, of the Maxwellian a type and having a hoop made of an elastic material. It is assumed that the disc is in an isothermal state under plane stress and rotates about its geometric axis with constant angular velocity w. It is assumed that this velocity varies in time according to Heaviside's function. At the time t = 0+ the disc is composed of two concentric rings, of which the elastic properties are different, in general. For t > 0, the outer ring remains elastic while the inner one changes its rheologic properties. At the common boundary of the two rings, continuity of radial displacement and stress is required. The paper shows that, contrarily to the case of homogeneous viscoelastic disc, the radial displacement at the edge of the disc tends asymptotically to a finite value if the time goes to infinity.